Structure-Based Stabilization of Non-native Protein–Protein Interactions of Coronavirus Nucleocapsid Proteins in Antiviral Drug Design - Lin, Shan-Meng; Lin, Shih-Chao; Hsu, Jia-Ning; Chang, Chung-ke; Chien, Ching-Ming; Wang, Yong-Sheng; Wu, Hung-Yi; Jeng, U-Ser; Kehn-Hall, Kylene; Hou, Ming-Hon (Journal of medicinal chemistry, 2020)
Structure-based stabilization of protein–protein interactions (PPIs) is a promising strategy for drug discovery. However, this approach has mainly focused on the stabilization of native PPIs, and non-native PPIs have received little consideration. Here, we identified a non-native interaction interface on the three-dimensional dimeric structure of the N-terminal domain of the MERS-CoV nucleocapsid protein (MERS-CoV N-NTD). The interface formed a conserved hydrophobic cavity suitable for targeted drug screening. By considering the hydrophobic complementarity during the virtual screening step, we identified 5-benzyloxygramine as a new N protein PPI orthosteric stabilizer that exhibits both antiviral and N-NTD protein-stabilizing activities. X-ray crystallography and small-angle X-ray scattering showed that 5-benzyloxygramine stabilizes the N-NTD dimers through simultaneous hydrophobic interactions with both partners, resulting in abnormal N protein oligomerization that was further confirmed in the cell. This unique approach based on the identification and stabilization of non-native PPIs of N protein could be applied toward drug discovery against CoV diseases.